Early Dynamics and Depth of Response in Multiple Myeloma Patients Treated With BCMA CAR-T Cells - Wong, Sandy W.; Shah, Nina; Ledergor, Guy; Martin, Thomas; Wolf, Jeffrey; Shui, Amy M.; Huang, Chiung-Yu; Martinez-Lopez, Joaquin (Frontiers in Oncology, 2021)
Chimeric antigen receptor T cell (CAR-T) therapy targeted against BCMA in multiple myeloma (MM) has produced rapid responses but many eventually relapse. In light of this new treatment, novel predictors of progression-free survival (PFS) are needed. We performed a single institution analysis of 54 BCMA-CAR-T patients. We analyzed patient’s overall response rate (ORR) by IMWG criteria, involved serum free light chains (iFLC), and minimal residual disease testing by next-generation sequencing (MRD-NGS). PFS differed significantly between patients who achieved a ≤SD and those who achieved a ≥PR (p<0.0001) though was not different between patients who achieved a ≥CR vs VGPR/PR (p=0.2). In contrast, patients who achieved a non-elevated iFLC at 15 days (p<0.0001, HR=6.8, 95% CI 2.7-17.3) or 30 days (p<0.001, HR=16.7, 95% CI 3.9-71.7) had a prolonged PFS compared to those with an elevated iFLC. Patients achieving MRD-NGS less than the detectable limit at a sensitivity of 10-6 had a better PFS than those with detectable disease at 1 month (p=0.02) and 3 months (p=0.02). In conclusion, achieving a non-elevated iFLC and not detected MRD-NGS quickly were strongly associated with improved PFS. Further studies are needed to confirm the role of these markers in MM patients receiving CAR-T therapies.